Bleak House - Dickens, Charles (Toronto ; New York Bantam Books, 1983)
Bleak House centers on the generations-long lawsuit Jarndyce and Jarndyce, through which whole families have inherited legendary hatreds. Focusing on Esther Summerson, a ward of John Jarndyce, the novel traces Esther's romantic coming-of-age and, in classic Dickensian style, the gradual revelation of long-buried secrets, all set against the foggy backdrop of the Court of Chancery
Keywords: England--London -- Illegitimate children -- Young women